On Question of Concept of Power in T. Hobbes Political Philosophy - Dymerets, Rostyslav (Sententiae, 2001)
The author affirms, that the essence of Thomas Gobbes philosophy lies in transformation law of nature into political power. Due to human equal rights, every particular human is weaker then the others. Hence for self-preservation of particular humans natural law has to be transformed into two distinct forms of power: into an absolute power of sovereign and into freedom of subjects, that from now on considers as an ability to obey to sovereign. If humans give to the sovereign power that is inverted to their ability of being humans, then sovereign has to be face of humans` ability to use their freedom, hence use humans as humans have to be used. Freedom to be a human is held by a human until she wants to be considered as human.